2018
DOI: 10.1167/iovs.17-22702
|View full text |Cite
|
Sign up to set email alerts
|

The Absence of Indoleamine 2,3-Dioxygenase Inhibits Retinal Capillary Degeneration in Diabetic Mice

Abstract: PurposeLoss of retinal capillary endothelial cells and pericytes through apoptosis is an early event in diabetic retinopathy (DR). Inflammatory pathways play a role in early DR, yet the biochemical mechanisms are poorly understood. In this study, we investigated the role of indoleamine 2,3-dioxygenase (IDO), an inflammatory cytokine-inducible enzyme, on retinal endothelial apoptosis and capillary degeneration in the diabetic retina.MethodsIDO was detected in human and mouse retinas by immunohistochemistry or W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Nahomi et al 54 reported that IDO1 played an important role in retinal endothelial apoptosis and capillary degeneration in the diabetic retina. They summarized four molecular mechanisms of IDO1 in endothelial cell apoptosis: (1) hyperglycemia enhanced IFN-c-mediated IDO1 expression; (2) increased IFN-c induced IDO1 in the retinal capillary endothelium; (3) oxidative stress regulated IDO1-mediated endothelial cell apoptosis; and (4) IDO1 deficiency in diabetic reduced the formation of acellular capillary.…”
Section: Function Of Ido or Tdo In Different Diseasesmentioning
confidence: 99%
“…Nahomi et al 54 reported that IDO1 played an important role in retinal endothelial apoptosis and capillary degeneration in the diabetic retina. They summarized four molecular mechanisms of IDO1 in endothelial cell apoptosis: (1) hyperglycemia enhanced IFN-c-mediated IDO1 expression; (2) increased IFN-c induced IDO1 in the retinal capillary endothelium; (3) oxidative stress regulated IDO1-mediated endothelial cell apoptosis; and (4) IDO1 deficiency in diabetic reduced the formation of acellular capillary.…”
Section: Function Of Ido or Tdo In Different Diseasesmentioning
confidence: 99%
“…Several studies, on the other hand, were performed by modifying KP enzyme expression in animal or human cells in tissue culture. Inhibition of the enzyme at a genetic level was found to be beneficial in animal models of bacterial (2) and viral (3, 4) infections, immune modulation following organ transplant (19, 20) and diseases in which chronic inflammation plays a crucial role, such as DR (27), atherosclerosis (28), AAA (29, 30) and metabolic changes linked to obesity (31). Inhibition of the enzyme is also a promising way of interfering in tumor mediated immunological changes, thus restoring anti-tumor immunity (33, 34, 36, 45, 46).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycaemia induced chronic retinal inflammation has a pivotal role in the development of diabetic retinopathy (DR), one of the major causes of visual impairment worldwide (120). In a recent study, Nahomi et al reported a 50 percent increase of the level of IFNγ in human diabetic retinas accompanied with elevated IDO expression (27). Genetic inhibition of IDO function in diabetic IDO −/− mice was found to reduce retinal capillary degeneration, as acellular capillary formation in knockout mice was alleviated as compared to their WT counterparts (27).…”
Section: Immunomodulation Via Altering the Expression Of Genes That Cmentioning
confidence: 99%
“…Capillary bed preparation of WT and KMO KO retinas and quantification of capillary degeneration were performed as previously described [63,64].…”
Section: Assessment Of Capillary Degeneration In the Retinamentioning
confidence: 99%
“…Male C57BL/6J mice at 3-months of age were made diabetic by i.p. administration of streptozotocin (STZ, MP Biomedicals, Solon, OH, USA), as previously described [64]. Diabetes was confirmed by the elevated fasting blood glucose after 1 week of STZ injection.…”
Section: Induction Of Diabetes In Micementioning
confidence: 99%